The Evolution of Indonesian Democracy: Challenges and Prospects in the Post-Reformasi Era - Alvaro Pratama; Fahmi Hidayat; Faizal Junaid (Indonesian Political Transformation, 2025)
Since the fall of the New Order regime in 1998, Indonesia has undergone significant political transformation, transitioning from an authoritarian regime to a vibrant democracy. This paper examines the evolution of Indonesian democracy in the post-Reformasi era, focusing on the challenges the country faces in consolidating democratic institutions and practices. Through a critical analysis of electoral systems, political parties, and civil society engagement, the study highlights the progress made in promoting political freedoms and human rights. However, it also addresses the persistent challenges of corruption, political polarization, and elite capture that continue to undermine democratic processes. The paper explores the role of the Indonesian people in shaping political change and the growing influence of social media in political discourse. The contribution of this research lies in its examination of the interplay between democratic reforms and political realities, offering insights into the future prospects of Indonesian democracy and the mechanisms needed to address its ongoing challenges.